3 - 4q = 10q + 10
3 - 10 = 10q + 4 q
- 7 = 14q
q = - 7/14
q = - 1 / 2
2007-10-11 10:48:17
·
answer #1
·
answered by Anonymous
·
0⤊
1⤋
Q=1
2016-05-21 23:20:35
·
answer #2
·
answered by ? 3
·
0⤊
0⤋
3 - 4q = 10q + 10
3 + -10 = 10q +4q
-7 = 14q
-7/14= -1/2
x = -1/2
2007-10-11 14:08:11
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
first thing is to put all the variables on one side and numbers on the other,
3-10=10q+4q remember to change signs as you hop over the equal sign
Then simplify
-7=14q
now divide both sides by 14
-7/14=q
simplify
-1/2 = q
hope this helps!
2007-10-11 10:49:57
·
answer #4
·
answered by car 3
·
0⤊
0⤋
ok... heres how we learned.
u need to get all of your numbers with variables on one side.
and all your numbers without on the other side of the equation.
in order to do that you must do the inverse or opposite of the number.
3-4q=10q+10
3-4q-10q=10
-4q-10q=10-3
-14q=7
divide by -14 on both sides and u are left with
q= -.5
sorry if its a bit unclear.
but i hope this helps =]
2007-10-11 10:52:21
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋
3 - 4q = 10q + 10? all same variables on same side
3=14q+10 subtract 10 from each side
-7=14q divides by -7 on both sides
q= -1/2
2007-10-11 10:48:47
·
answer #6
·
answered by pkrplyr707 3
·
0⤊
0⤋
3 - 4q = 10q + 10
-4q = 10q + 10 - 3
-4q = 10q + 7
-4q -10q = 7
-14q = 7
q = -7/14
q = -1/2
2007-10-11 10:49:54
·
answer #7
·
answered by Dr. WD 5
·
0⤊
1⤋
3-4q=10q+10
-4q=10q+7
-14q=7
q=-2
2007-10-11 10:53:09
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
3-4q=10q+10
or 3-3-4q=10q+10-3
or -4q=10q+7
or -4q-10q=10q-10q+7
or -14q=7
or q=-7/14=-1/2 ans
2007-10-11 10:58:26
·
answer #9
·
answered by MAHAANIM07 4
·
0⤊
0⤋
-4q-10q=10-3
the rest is you
2007-10-11 10:48:16
·
answer #10
·
answered by mishkin 5
·
0⤊
0⤋